The Political Economy of Oil in Venezuela : Class Conflict, the State, and the World Market - Ciupa, Kristin, (Historical Materialism Book Series ;, 2026)
The Political Economy of Oil in Venezuela re-examines oil dependency debates, situated within an analysis of Venezuela's Bolivarian Process from 1999-2016. Drawing on interviews with Venezuelan politicians, economists, scholars and activists, as well as extensive archival research, the book explores the potential for class struggle to shape national oil development and conditions of oil dependency. It situates Venezuela's Bolivarian Process within a broader regional shift to the left in Latin America, the structures of the global oil market and Venezuela's role as oil-exporter in the global economy, popular class struggle in Venezuela arising out of the neoliberal period, and the history of Venezuelan rentier accumulation. Ultimately, the book explores the question of agency in conversation with structural analyses of rent and natural resource dependency.